Developing the intercultural competence of early childhood preservice teachers: preparing teachers for culturally diverse classrooms. Issue 1 (2nd January 2022) - Lash, Martha; Madrid Akpovo, Samara; Cushner, Kenneth
ABSTRACT: This research reports on studies conducted in two early childhood education (ECE) teacher preparation programs focused on increasing preservice teachers' intercultural competence through intercultural teaching and learning and diverse US and international field experiences. Study 1 took place at a large U.S. Midwestern university with the first cohort (n = 43) of preservice teachers to have completed the revised internationally focused program. Study 2 took place at a midsized rural university in the U.S. Rocky Mountain region with preservice teachers (n = 9) who completed an eight-month university-led program with Nepal field experience. The researchers used the same instrument to measure preservice teachers' intercultural sensitivity – the Intercultural Development Inventory (IDI) – before and after completion of the respective programs. The Statistical Package for the Social Sciences was used for the analysis of the IDI scores of participants; paired samples t -test yielded individual and composite results. IDI pre and post results showed statistically significant increases in the composite scores for preservice teachers' levels of intercultural competence for most participants. Attributes of movement away from trivializing other cultures and toward recognizing cultural similarities, appreciation of and curiosity about cultural differences, and the ability to interpret phenomena taking place in a cultural context became evident.